2020
DOI: 10.3390/brainsci10080543
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Deficits in Juvenile Onset Huntington’s Disease

Abstract: Reports of behavioral disturbance in Juvenile-Onset Huntington’s Disease (JOHD) have been based primarily on qualitative caregiver reports or retrospective medical record reviews. This study aims to quantify differences in behavior in patients with JOHD using informant- and self-report questionnaires. Informants of 21 children/young adults (12 female) with JOHD and 115 children/young adults (64 female) with a family history of Huntington’s Disease, but who did not inherit the disease themselves (Gene-Non-Expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
(44 reference statements)
2
3
0
Order By: Relevance
“…Among the peculiarities we highlight in our study, we describe and confirm the high occurrence of sleep disorders in affected young children, in line with previous reports on JOHD [14]. We also confirm the occurrence of seizures as a common feature in PHD [8,[31][32][33]. Furthermore, we report the occurrence of drooling, dysphagia, stereotypic movements and apraxia during the first phases of the disease, all features that may concur to worsen the disease severity and shorten the patients' life span, as described [8].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the peculiarities we highlight in our study, we describe and confirm the high occurrence of sleep disorders in affected young children, in line with previous reports on JOHD [14]. We also confirm the occurrence of seizures as a common feature in PHD [8,[31][32][33]. Furthermore, we report the occurrence of drooling, dysphagia, stereotypic movements and apraxia during the first phases of the disease, all features that may concur to worsen the disease severity and shorten the patients' life span, as described [8].…”
Section: Discussionsupporting
confidence: 93%
“…So far, all studies concerning cognitive and behavioral changes in PHD cohorts have been performed by caregiver-based, self-reported, retrospective descriptions, with no focus on specific and comprehensive evaluations [8,9,16] or by caregiver survey [14,31]. Few studies reported a retrospective analysis in JOHD with neuropsychological examinations only performed in young adults (i.e., aged 20 years) and almost never in affected kids, generally showing limited length mutations [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of the first symptom is a challenging task even in cases with a family history of HD; the delay has been reported to be up to 9 years. Our results reinforce the relevance of the cognitive and psychiatric symptoms in patients with JHD, unlike adult HD; these clinical manifestations need to be investigated in more detail to avoid diagnosis delay [39].…”
Section: Discussionsupporting
confidence: 78%
“…This may suggest that to identify subtle deviations between different disease epochs above and beyond already established knowledge, collecting continuous longitudinal data for longer periods and with more times per participant (eg, collecting annual data for >10 years) is required. This, also together with other factors including follow‐up of younger, more diverse samples, 40,41 could be argued as being more important than having a bigger sample with follow‐up of 4–5 years. This further supports previous discussions on the importance of investing in long‐term longitudinal studies that span 5 years or more with annual follow‐up, which has been posited for HD 42,43 as well as other neurodegenerative diseases like Alzheimerʼs disease 44,45 .…”
Section: Discussionmentioning
confidence: 99%